Ecofeminist Theology: Intersectional Justice and Plumwood’s Philosophical Animism - Carfore, Kimberly (Feminist theology, 2021)
The multi-faceted ecological crisis—combining problems of ecology, society, and religion—is tied to the ideologies implicit in Western thinking. In this essay, I outline an ecofeminist theology which addresses how the current ecological crisis we face—including but not limited to, climate change, mass species extinction, ocean acidification, the rise in wildfires and superstorms, glacial melt, pollution—are tied to problematic and incorrect ideologies. To do this, I utilize Val Plumwood’s robust ecofeminist philosophy to revealing harmful dualisms implicit in all forms of oppression. I critique transcendental monotheism for extracting life, God, and agency from the natural world. If God exists over and above the Earth, and this God is omnipotent, omnipresent, and omniscient, this justifies the problematic lagged response to our urgent ecological crisis. In short, my ecofeminist theology (1) affirms intersectionality. It considers racial injustice and systemic racism are intertwined with the ecological crises. We cannot address our ecological crisis without also addressing racial injustice. (2) It critiques a transcendental monotheistic God as this reinforces irresponsible and apathetic responses to our multi-faceted ecological crisis. And (3) it affirms Plumwood’s “philosophical animism” as a way to retrieve nature in the active voice. By retrieving nature in the active voice, we retrieve a sense of groundedness in place through relationships with non-humans. Her “philosophical animism” affirms agency in the natural world without culturally appropriating Indigenous cultures. It is a way for Westerners to enter into dialogical relationship with the natural world. It is both political—affirming the rights of Black, Indigenous, and other people of color—and it is personal—engaging in a practice of the wild (Gary Snyder).